War and Postwar Violence - Gartner, Rosemary (Crime and justice, 2018)
Wars are related to subsequent violence in complex and at times contradictory ways. The relationships between war and postwar violence, recognized throughout history, have attracted the attention and concern of researchers, state officials, and policy makers and the broader public. Methodological challenges, however, limit the potential for isolating the precise circumstances under which war and postwar violence are causally related. The weight of the evidence indicates that war is often followed by increases in violence, but there are important exceptions to this pattern. Potential theoretical explanations for this relationship abound. The harmful effects of wars on the minds and bodies of those participating in them are less influential on postwar violence than are the damages wars do to postwar societies’ social and economic institutions, political legitimacy, and group relations. Preventing or reducing elevated rates of violence after wars is rarely a priority during peace negotiations. As a consequence, policies instituted as part of the peace-building process often fuel violent crime.